Traditional Chinese medicine for non-alcoholic fatty liver disease: an overview of systematic reviews with evidence mapping and metabolic outcome assessment - Li, Juanjuan; Jiao, Ruimin; Su, Wenquan; Chen, Wei; Hu, Xiangyu; Xu, Shuai; Xu, Lie; Yao, Weiwei; Liu, Kejia; You, Hong; Zhao, Jingjie (Frontiers in Pharmacology, 2025)
The paradigm shift from non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated fatty liver disease (MAFLD) emphasizes metabolic pathogenesis, yet the efficacy of Traditional Chinese Medicine (TCM) under this framework remains unevaluated. Prior reviews focused on NAFLD with outdated data (<2020), lacking clinical translation tools and methodological standards for TCM systematic reviews and meta-analyses (SRs/MAs). This overview integrates NAFLD criteria, visualizes TCM efficacy via evidence mapping, proposes a methodological framework to standardize TCM SRs/MAs, and focuses on evaluating metabolism-related indicators. Nine databases were searched (from database inception to December 30, 2024) for TCM SRs/MAs in NAFLD. Methodological quality was assessed via AMSTAR-2, PRISMA/PRISMA-CHM, and GRADE. Evidence mapping visualized outcomes (liver enzymes, metabolism) to identify clinical priorities. Standardized reporting guidelines for TCM preparations were adhered to, and a ConPhYMP tool assessment evaluated botanical drugs composition and processing disclosure. Thirty-seven SRs/MAs (35 low/critically low quality) reported trends of reduced ALT (−8.2 U/L, 95% CI: −10.1 to −6.3), improved metabolic parameters (e.g., TG: −0.5 mmol/L), and enhanced B-ultrasound resolution (RR: 1.62), though these findings are limited by methodological flaws and low-quality evidence. Evidence mapping highlighted Xiaoyao Powder and Danning Tablet as top-performing formulas. A methodological framework addressing TCM heterogeneity (formula standardization, dosage) and reporting biases was proposed. This is the first overview integrating NAFLD criteria to visualize TCM-related evidence, offering preliminary observations on potential associations between TCM interventions and metabolic outcomes in NAFLD (interpreted with caution due to low evidence quality). The evidence map and methodological guidelines provide a foundation for standardized future TCM research, while clinical translation of current findings is not recommended due to insufficient high-quality evidence.